Lighting Retrofit Scheme Economic Evaluation - Mohd Firdaus Mohd Ab Halim; Umar Al-Amani Azlan; M. Haniff Harun; Khalil Azha M. Annuar; S. Halma Johari; A. Rahim Abdulla; M. Faisal Hushim (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
In this paper, two lighting retrofit scheme is simulated to evaluate the amount of saving that the commercial building owner would benefits. Simple payback period and net present value are the method used to qualify the retrofit scheme to be profitable or otherwise. The analysis include the effect of electricity price, energy saving percentage, technology price and efficacy future values towards the economic return. The retrofit scheme presented only covers for the building that already has existing lighting equipment and comply towards the standard set by the international technical society. All variables and assumption are based on latest report by the world governing bodies and regulation.